Mastering Vocabulary by Using CrosswordPuzzle - Vivin Krismawati Modjanggo (Sintuwu Maroso Journal of English Teaching, 2017)
The objective of this research is to find out whether crossword puzzle is effective in improving students’ vocabulary mastery. The sample of this research is the eight grade students of SMP GKST I Tentena particularly class VIIIC and VIII A. This research is quasi experimental design- the nonequivalent control group design, that involved two sample groups, they are experimental group and control group. The researcher uses clustering sampling. The researcher applies test instrument (Pre-test and Post-test) in collecting the data. The pre-test is administered to measure the students’ achievement in learning vocabulary before treatment, while the post-test is administered to measure the students’ achievement after treatment. Based on the result of the study, it is proved that the application of crossword puzzle is affective in improving students’ vocabulary mastery. It is found that the tcounted (1.820) is higher that t-table (1.693). It means that the hypothesis of this research is accepted. In conclusion, the achievement of the eight grade students of SMP GKST I Tentena in mastering vocabulary can be improved significantly by using crossword puzzle.Keywords: Crossword Puzzle, Improve, Vocabulary Mastery